Iranian nurses' perspective of barriers to sexual counseling for patients with myocardial infarction - Parvin Mangolian Shahrbabaki; Roghayeh Mehdipour-Rabori; Tayyebeh Gazestani; Mansooreh Azzizadeh Forouzi (BMC, 2021)
Abstract Background Sexual counseling is an essential part of cardiac rehabilitation. This study aimed to investigate Iranian nurses' perceptions of barriers to sexual counseling for patients with myocardial infarction. Methods This cross-sectional study included 169 nurses who worked in CCUs, Post CCUs, and cardiac surgery wards of teaching hospitals in southeastern Iran. The barriers to providing sexual counseling inventory was used to assess sexual counseling barriers for patients with myocardial infarction. SPSS 19 was used to analyze the data. The significance level was 0.05. This study lasted from November 2019 to March 2020. Results The results showed that the highest mean scores for patient-related barriers were related to the patient's religion and belief (2.83 ± 0.52) and embarrassment (2.82 ± 0.52 %). The highest scores for nurse-related barriers were related to nurse's discomfort in discussing sexual issues (2.67 ± 0.62), a lack of experience in sexual counseling (2.62 ± 0.65), and sexual hesitation in advising patients (2.57 ± 0.7). The highest mean scores for organizational barriers were a lack of managerial attention and support for counseling (2.67 ± 0.66) and a lack of proper supervision system (2.62 ± 0.72). Conclusions Religion/beliefs, embarrassment and a lack of managerial attention and support for counseling were the most important barriers in the organizational, nursing and patient domains. Since sexuality is a significant issue in most cultures and religions, particularly in Islamic countries, health care professionals should work to change the attitudes of patients towards sexuality through sexual health education and counseling to meet patients' needs and improve their sexual health.